Vergine giurata - Rohrwacher, Alba 1979-; Kodheli, Flonja; Eidinger, Lars 1976-; Manieri, Francesca 1979- (CG Entertainment, 2016)
A young woman named Hana who lives in an Albanian village ruled by men, takes an oath of eternal virginity to live as a sworn virgin, becoming Mark, so she can live free as a man. Years later, restless and feeling imprisoned by his choice, Mark leaves for Italy to visit his sister and family. There, he explores the unexpected pleasures of attraction and the body and decides to abandon Mark, rediscovering herself/himself as Hana, to become a new and liberated person
Based on the novel by Elvira Dones. - Originally produced as a motion picture in 2015. - Extras: "In cerca de film" - making of. - format 16/9 - 2,35:1
Keywords: Sex role / Albania / Drama; Male impersonators / Albania / Drama; Sisters / Albania / Drama; Frau; Albania / Women / Social conditions / Drama; DVD-Video